Pengaruh E-Handout Berbasis Predict, Observe, Explain (POE) Terhadap Pemahaman Konsep Siswa pada Materi Getaran Harmonik - Puji Purdhiyah; Hadma Yuliani; Jhelang Annovasho (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
This study aims to determine the effect of students' understanding of the concept after usinge-handout based on POE on students' harmonic vibration material. This type of research is a quantitative study using pre-experimental methodsone group pretest-posttest design. The research instrument was a concept understanding test consisting of 12 questions. The data obtained from the analysis of understanding the concept gets an averagepretest of 32.333 and posttest of 79.933. The results of the analysis wit hpaired samples t-test ie tcount < ttablenamely 0.000 <0.05. So it can be concluded that there is an effect after using the POE-based e-handout on students' understanding of concepts.